2019 18th IEEE International Conference on Machine Learning and Applications (ICMLA) 2019
DOI: 10.1109/icmla.2019.00165
|View full text |Cite
|
Sign up to set email alerts
|

Optic-Net: A Novel Convolutional Neural Network for Diagnosis of Retinal Diseases from Optical Tomography Images

Abstract: Diagnosing different retinal diseases from Spectral Domain Optical Coherence Tomography (SD-OCT) images is a challenging task. Different automated approaches such as image processing, machine learning and deep learning algorithms have been used for early detection and diagnosis of retinal diseases. Unfortunately, these are prone to error and computational inefficiency, which requires further intervention from human experts. In this paper, we propose a novel convolution neural network architecture to successful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The generator block consists of two generator modules, the fine and coarse generators, which are designed in a U-shaped encoder-decoder manner. The coarse generator is comprised of a reflection+padding block, three convolution (Conv)+batch normalization (BN)+leaky rectified linear units (ReLU), and four novel residual blocks 44,45 (ResBlk), followed by two transpose convolution (Deconv), one reflection+padding, one Conv, and an output activation layers ( Fig. 1B-left), and is responsible for generating coarse and global structures of the FA image such as the structures of the macula, optic disc, color, contrast, and brightness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The generator block consists of two generator modules, the fine and coarse generators, which are designed in a U-shaped encoder-decoder manner. The coarse generator is comprised of a reflection+padding block, three convolution (Conv)+batch normalization (BN)+leaky rectified linear units (ReLU), and four novel residual blocks 44,45 (ResBlk), followed by two transpose convolution (Deconv), one reflection+padding, one Conv, and an output activation layers ( Fig. 1B-left), and is responsible for generating coarse and global structures of the FA image such as the structures of the macula, optic disc, color, contrast, and brightness.…”
Section: Resultsmentioning
confidence: 99%
“…Deep learning conditional generative adversarial network. This study proposes a new conditional generative adversarial network (GAN) comprising of a novel residual block 44,45 for producing realistic FA from retinal fundus images. We use two generators ( G fine and G coarse ) in the proposed network, as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it extracts and preserves depth and spatial features while forward propagating the network. Recent advancement in retinal image classification has shown that combining separable convolutional layers with dilation allows for more robust feature extraction [19]. We design two unique residual identity blocks, for our generators and discriminators, as illustrated in Fig.…”
Section: Distinct Identity Blocks For Generator and Discriminatormentioning
confidence: 99%